2010
DOI: 10.1007/s11814-010-0243-2
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium removal from aqueous solutions using biosorbent Syzygium cumini leaf powder: Kinetic and equilibrium studies

Abstract: Syzygium cumini L. leaf powder and Cd(II) loaded samples were characterized using FTIR and SEM techniques. The biosorption of cadmium ions from aqueous solution was studied in a batch adsorption system as a function of pH, contact time, adsorbate, adsorbent, anion and cation concentrations. The biosorption capacities and rates of transfer of cadmium ions onto S. cumini L. were evaluated. The kinetics could be best described by both linear and nonlinear pseudo-second order models. The isothermic data fitted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…1). The better fitting of pseudo-second-order model as compared to the first-order-model for cation adsorption on different adsorbents has been reported by a number of researchers [13,14,[17][18][19].…”
Section: Effect Of Contact Timementioning
confidence: 92%
See 1 more Smart Citation
“…1). The better fitting of pseudo-second-order model as compared to the first-order-model for cation adsorption on different adsorbents has been reported by a number of researchers [13,14,[17][18][19].…”
Section: Effect Of Contact Timementioning
confidence: 92%
“…Besides the agriculture wastes, leaves of various trees which are also waste and are usually dumped into garbage cans can be potential adsorbents for mitigation of heavy metal ions. Studies have been reported on dried leaf powders of various trees such as neem [10], olive [11], rubber [12], teak [13], and jamun [14] for Cd(II) adsorption from aqueous solutions. The present work is an attempt in the direction of finding an alternate, cheap, green biosorbent for treatment of effluents laden with cadmium.…”
Section: Introductionmentioning
confidence: 99%
“…Recently many reviews have been published highlighting use of agricultural low cost waste materials for the removal of heavy metals [8][9][10][11][12][13][14]. Some of the adsorption processes developed for removal of cadmium using biosorbents include tea waste [15,16], food waste [17], sugarcane bagasse [18], degreased coffee seeds [19], apple residue [20,21], saw dust [22][23][24], eucalyptus bark [25] mango peel waste [26], rice husk [27] and leaf powders [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The biosorption on dried leaves is attributed to their protein, carbohydrates, and phenolic compounds which have metal binding functional groups such as carboxyl, hydroxyl, sulfate, phosphate, and amino. Many researchers have investigated usefulness of various types of leaves with or without pretreatment 10–14 for removal of Cd(II) from wastewaters.…”
Section: Introductionmentioning
confidence: 99%